Utilization of Lanthanum-Modified Seed Crystals Produced Via Microbiological Production for the Purification of Calcium and Phosphorus from Household Wastewater - V. R. Raji (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The synthesis of lanthanum-modified seed crystals via microbial mediation and their subsequent application in removing phosphorus and calcium from domestic wastewater is the focus of this study. Through the action of microorganisms, particularly Pseudomonas aeruginosa, lanthanum is incorporated into the seed crystals, enhancing their performance in wastewater treatment. The research demonstrates notable success in utilizing these modified seed crystals for wastewater treatment, with impressive removal efficiencies observed for both phosphorus and calcium. After multiple applications, significant reductions were achieved, with phosphorus removal reaching 94% and calcium removal at 60%. This study delves into the underlying mechanisms driving this enhanced performance, identifying key processes such as chemisorption, intra-particle diffusion, electrostatic contact, ligand exchange, and induced crystallization. Understanding these mechanisms is crucial for optimizing the design and operation of wastewater treatment systems utilizing these modified seed crystals. These experiments validate the efficacy of the modified seed crystals across different scenarios, particularly highlighting their superior performance in phosphorus removal, with an efficiency of 95%. Given the current environmental challenges posed by wastewater pollution and the increasing demand for sustainable treatment technologies, the development of lanthanum-modified seed crystals holds significant promise. Their application in domestic wastewater treatment presents a viable and effective solution, offering a pathway towards cleaner and healthier water resources. Its appeal extends to both developed and developing nations, offering flexibility to adapt to local needs by integrating it with conventional (above-ground) natural or engineered water and wastewater treatment technologies.